2012
DOI: 10.1094/pdis-06-11-0466
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Resistance Potential of Selected Fungicides to Galactomyces and Penicillium spp. Causing Postharvest Fruit Decays of Citrus and Other Crops

Abstract: McKay, A. H., Förster, H., and Adaskaveg, J. E. 2012. Toxicity and resistance potential of selected fungicides to Gaiactomyces and Pénicillium spp. causing postharvest fruit decays of citrus and other crops. Plant Dis. 96:87-96.A diverse collection of isolates of Gaiactomyces citri-aurantii and G. geotrichutn, the causal pathogens of sour rots of citrus and other fruit crops, respectively, was evaluated for sensitivity to demethylationinhihiting (DMI) fungicides of the triazole group. Propiconazole was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Multiple resistance have been reported for IMZ, TBZ and SOPP (Holmes and Eckert, 1999). Imazalil and PPZ fall in the same DMI class, and cross resistance has been shown between these two fungicides (Mckay et al, 2012b). Some indication of potential negative cross resistance was also observed where the IMZ resistant isolates were markedly better controlled with GRA, PYR and AZO than their respective control of the sensitive isolates.…”
Section: Discussionmentioning
confidence: 95%
“…Multiple resistance have been reported for IMZ, TBZ and SOPP (Holmes and Eckert, 1999). Imazalil and PPZ fall in the same DMI class, and cross resistance has been shown between these two fungicides (Mckay et al, 2012b). Some indication of potential negative cross resistance was also observed where the IMZ resistant isolates were markedly better controlled with GRA, PYR and AZO than their respective control of the sensitive isolates.…”
Section: Discussionmentioning
confidence: 95%
“…A molecular analysis of the fungi that were isolated from the municipal sewage sludge indicated that this sludge could be dangerous for plants due to the presence of M. circinelloides and G. citri-aurantii . These fungal species are common plant pathogens [ 41 , 42 ]. Worldwide citrus sour rot, which is caused by Geotrichum citri-aurantii , has been reported as an important postharvest disease in citrus fruit [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…These fungal species are common plant pathogens [ 41 , 42 ]. Worldwide citrus sour rot, which is caused by Geotrichum citri-aurantii , has been reported as an important postharvest disease in citrus fruit [ 42 ]. In addition, M. circinelloides causes disease in fruit [ 41 ] and tomatoes [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The resulted economic losses are so great that aroused enormous attentions all over the world [1]. The sterol demethylation inhibitor (DMI) fungicides, such as imazalil and prochloraz, have been widely applied to control citrus molds [2][3][4][5][6]. However, resistance to these DMI fungicides has frequently occurred for the Penicillium molds in the past decade, especially for P. digitatum isolates with high DMIresistance [5,7], considerably reducing the efficacy of the fungicides.…”
Section: (Continued From Previous Page)mentioning
confidence: 99%